2023
DOI: 10.3390/su151813643
|View full text |Cite
|
Sign up to set email alerts
|

Steady and Unsteady Flow Characteristics inside Short Jet Self-Priming Pump

Hao Yu,
Chuan Wang,
Guohui Li
et al.

Abstract: Due to their great efficiency and minimal loss, self-priming jet pumps are frequently employed in a variety of sectors for sustainable development. A short jet self-priming pump’s steady and unsteady flow characteristics are investigated numerically in this study using a standard k-ε turbulence model. The precision and dependability of the numerical calculations used in this work are demonstrated by the less than 2% difference between the pump performance data from the numerical calculation and the external ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Based on the above study, it was found that although the flow direction of the medium within the traditional jet pump system is the same as that of the impeller inlet medium, there are still problems with its hydraulic performance and operational stability (Saker and Hassan, 2013;Sharifi, 2020;Wang et al, 2019). In order to meet the requirements of limited installation space in engineering practice, a more compact structure, a smaller size of the short section, of the jet pump was proposed (Yang et al, 2023;Yu et al, 2023). The jet pump positions the ejector structure perpendicular to the impeller, significantly reducing the overall footprint of the jet pump.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above study, it was found that although the flow direction of the medium within the traditional jet pump system is the same as that of the impeller inlet medium, there are still problems with its hydraulic performance and operational stability (Saker and Hassan, 2013;Sharifi, 2020;Wang et al, 2019). In order to meet the requirements of limited installation space in engineering practice, a more compact structure, a smaller size of the short section, of the jet pump was proposed (Yang et al, 2023;Yu et al, 2023). The jet pump positions the ejector structure perpendicular to the impeller, significantly reducing the overall footprint of the jet pump.…”
Section: Introductionmentioning
confidence: 99%
“…Following decades of development, research on the internal flow of these pumps has become increasingly profound. With the continuous development of computer technology, Computational Fluid Dynamics (CFD) techniques have been adopted for the in-depth study of flow [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…These vortices undergo continuous deformation, rupture, merging, and evolution into turbulence during their movement. Consequently, they entrain surrounding fluid into the jet region, facilitating the transfer of momentum, heat, and mass between the jet and its ambient environment [1][2][3]. Therefore, numerous scholars have carried out detailed studies on the scouring characteristics associated with jets.…”
Section: Introductionmentioning
confidence: 99%